The Inculturation of Islam in the Dongkrek Folklore as a Plague Expeller - Ari Jalu Nur Khowin; Erwin Yudi Prahara; Ahmad Zubaidi (Ushuluddin, Adab, and Dakwah Faculty of State Islamic University Ponorogo, 2024)
Islam is a theological teaching based on God's revelation, different from culture, which is a product of human creation. This study uses qualitative methods with discourse analysis, linking field data, opinions, and theories to understand the inculturation of Islam in the Dongkrek folklore in Mejayan. The results align with Dundes' theory, which states that the Dongkrek folklore functions to strengthen community solidarity and uphold norms. Dongkrek combines Javanese ritual elements and Islamic prayers, demonstrating a process of inculturation in this ritual to expel the plague in the village of Mejayan. Additionally, Dongkrek serves as a coercive and supervisory tool, projecting collective imagination and ensuring adherence to community norms. The Mejayan government strives to maintain Dongkrek’s optimal function in strengthening the social life of the community, which is harmonious, peaceful, and united. Dongkrek illustrates the blending of Javanese culture and Islamic teachings, showing clear evidence of inculturation in this ritual.